PREPATION AND IMPLEMENTATION MARKETING PLAN: SOCIAL MEDIA MARKETING PROGRAM AT SUBANG HOSPITAL - Gugyh Susandy; Mutqi Sopiawadi; Edi Susanto; Feti Khoerunnisa; Rizal Septiana (STIESA-PRESS, 2023)
Health promotion is a process of community empowerment through informing and influencing activities. Along with developments in time and technology, social media has developed which is considered to be an effective and efficient health promotion medium. Social media is a medium that makes it easier for people to get information about various things because social media can be easily accessed by all groups. The descriptive research method uses a qualitative approach, so the data that has been collected will be analyzed more deeply in a qualitative descriptive manner. The data will be arranged systematically and explained in words that provide a clearer picture. The results of a systematic review of this research show how effective and important the use of social media is in marketing trends in hospitals and it turns out that many hospitals in their marketing use more than one social media platform in order to influence reputation, increase trust and sharing as one of the hospital's marketing strategies.